Describing hospital utilisation and associated factors following stroke using linked clinical registry and hospital administrative data. (2018) - Andrew, Nadine; Kilkenny, Monique; Sundararajan, Vijaya; Kim, Joosup; Thrift, Amanda; Johnston, Trisha; Grimley, Rohan; Gattellari, Melina; Katzenellenbogen, Judith; Lannin, Natasha; Boyd, James; Flack, Felicity; et al.
No abstract available